Prognosis and treatment of complications associated with COVID-19: a systematic review and meta-analysis - Xudong Xie; Liangcong Hu; Hang Xue; Yuan Xiong; Adriana C. Panayi; Ze Lin; Lang Chen; Chenchen Yan; Wu Zhou; Bobin Mi; Guohui Liu (Compuscript Ltd, 2022)
The Coronavirus Disease 2019 (COVID-19) pandemic has been estimated to have claimed more than 6 million lives, and most deaths have been attributed to complications non-specific to the virus. Therefore, understanding and treating these complications are imperative. In this meta-analysis, we reviewed 181 studies published in early stages of the COVID-19 pandemic. We presented that the complications with high incidence among all COVID-19 cases were acute respiratory distress syndrome (ARDS, 18.52%), respiratory failure (16.54%), liver injury (14.13%) and multiple-organ dysfunction syndrome (MODS, 13.62%). Among patients who died, the most common complications were ARDS (84.10%), respiratory failure (78.75%) and respiratory injury (75.72%). Subsequently, we analyzed the risk factors for complications, and reviewed the currently available therapies according to complications and prognosis. To decrease the prevalence of COVID-19 complications and mortality, healthcare workers and patients should pay greater attention to the complications identified herein, particularly those occurring preclinically.